Development of a new multiplex real-time PCR assay for rapid screening of hospital-acquired infection agents - İstanbullu Tosun, Ayşe; Kolukırık, Mustafa; Yılmaz, Mesut; Nar Ötgün, Selin; Aygün, Gökhan; Ketre Kolukırık, Canan Zöhre; Zeybek, Ümit; Girgin Özgümüş, Gözde; Turan, Meral; Kuşkucu, Mert; İnce, Orhan; İnce, Bahar; et al. (Elsevier B.V., 2023)
Aims: A new multiplex real-time PCR (qPCR) assay was developed to detect antibiotic-resistant hospital-acquired infectious agents in nasal and rectal swab samples in 1.5 h without the need for nucleic acid extraction. Methods: Spiked negative clinical specimens were used for the analytical performance evaluation. Double-blind samples were collected from 1788 patients to assess the relative clinical performance of the qPCR assay to the conventional culture-based methods. Bio-Speedy® Fast Lysis Buffer (FLB) and 2× qPCR-Mix for hydrolysis probes (Bioeksen R&D Technologies, Istanbul, Turkey) and LightCycler® 96 Instrument (Roche Inc., Branchburg, NJ, USA) were used for all molecular analyses. The samples were transferred into 400 L FLB, homogenized and immediately used in qPCRs. The target DNA regions are vanA and vanB genes for vancomycin-resistant Enterococcus (VRE); blaKPC, blaNDM, blaVIM, blaIMP, blaOXA-23, blaOXA-48, blaOXA-58 genes for carbapenem-resistant Enterobacteriaceae (CRE); and mecA, mecC and spa for methicillin-resistant Staphylococcus aureus (MRSA). Results: No qPCR tests produced positive results for the samples spiked with the potential cross-reacting organisms. The limit of detection (LOD) of the assay for all targets was 100 colony-forming unit (cfu)/swab-sample. Results of the repeatability studies in two different centers were in 96%–100% (69/72–72/72) agreement. The relative specificity and sensitivity of the qPCR assay were respectively 96.8% and 98.8% for VRE; 94.9% and 95.1% for CRE; 99.9% and 97.1% for MRSA. Conclusions: The developed qPCR assay can screen antibiotic-resistant hospital-acquired infectious agents in infected/colonized patients with an equal clinical performance to the culture-based methods.
Keywords: Carbapenem-Resistant Enterobacteriaceae; Hospital-Acquired Infection; Methicillin-Resistant Staphylococcus Aureus; Real-Time PCR; Vancomycin-Resistant Enterococcus